Synergistically enhanced thermoelectric properties in n-type Bi6Cu2Se4O6 through inducing resonant levels. (15th June 2022) - Zheng, Junqing; Hong, Tao; Wang, Dongyang; Qin, Bingchao; Gao, Xiang; Zhao, Li-Dong
Abstract: Oxygen-containing semiconductors are considered to be promising thermoelectric materials because of the high physicochemical stability. New layered oxyselenide Bi6 Cu2 Se4 O6 possesses intrinsic low lattice thermal conductivity and can be modulated to n -type semiconductor through halogen doping, which is considered as a potential n -type thermoelectric oxide. In this work, first-principles calculations are utilized to obtain the electronic and phonon band structures for deeply recognizing the transport features of intrinsic Bi6 Cu2 Se4 O6 . Furthermore, Nb is selected as donor dopant in Bi6 Cu2 Se3.6 Cl0.4 O6, realizing a significantly improved power factor of ∼ 4.3 μV cm −1 K −2, which originates from the simultaneously optimized carrier concentration by effective doping and strengthened effective mass by inducing resonant levels around Fermi level. Meanwhile, the enhancement of phonon scattering are introduced, leading to a low lattice thermal conductivity of ∼ 0.68 W m −1 K −1 . Finally, thanks to the effective doping of Nb and the introduction of resonant levels, a maximum ZT ∼ 0.4 at 873 K and an average ZT ∼ 0.21 from 303 to 873 K can be obtained in n -type Bi5.91 Nb0.09 Cu2 Se3.6 Cl0.4 O6 . This study broadens the applicability of resonant levels to optimize performances of thermoelectric oxides, and promotes the potential application of n -type Bi6 Cu2 Se4 O6 -based thermoelectric materials in medium temperature range. Graphical abstract: Image, graphical abstract